Anatomical Variations of the Suprascapular Notch and Its Importance in Nerve Entrapment - Adnan Badar, Salman Yunas, Atif Hussain, Sadaf Shaheen, Abdul Rashid Baloch, Abdul Hafeez Baloch, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Entrapped neuropathy syndrome could be effectively managed with detailed anatomical knowledge of suprascapular notch. Suprascapular nerve injuries are now widely acknowledged as a cause of shoulder pain and dysfunction. The present study aimed to determine the anatomical variation of the suprascapular notch and its importance in nerve entrapment. Methodology: A total of 128 human scapulae of either gender were taken from the department of Anatomy, Saidu Group of Teaching Hospitals, Swat and Women Medical and Dental College Hospital Abbottabad during the period from January to June, 2021. Four parameters of Suprascapular notch (SSN) i) Superior transverse depth (STD), ii) Maximum depth (MD), iii) middle transverse diameter (MTD), and total circumferential diameter (TCD) were defined based on incisura inferior border shape and vertical diameters. Suprascapular notch presence or absence was grossly examined for all the scapulae. Vernier caliper was used for the measurement of the four suprascapular notch parameters. SPSS version 23 was used for data analysis. Results: Out of 128, 61 (47.7%) were right-sided and 67 (52.3%) were left-sided human scapulae. The prevalence of U-shaped, V-shaped, and J-shaped notch were 62 (48.4%), 27 (21.1%), and 13 (10.2%) respectively. The incidence of the large double foramen, complete, and incomplete suprascapular notch were 2 (1.6%), 7 (5.5%), and 8 (6.3%) respectively. W-notched was present in 3 (2.3%) scapulae whereas 6 (4.7%) scapulae had no notch. The vertical and transverse diameters for right and left-sided type-II scapulae were 4.9±2.1 mm and 8.9±3.1 mm and 4.8±1.7 mm and 9.1±2.3 mm respectively. Conclusion: The prevalence of U-shaped and V-shaped notch was 48.4% and 21.1% respectively. Suprascapular notch morphology could be determined with anatomical knowledge and play a critical role for neurosurgeons, clinicians, orthopedic surgeons, and radiologists for proper diagnosis and management of shoulder region surgical procedure and protocol.